How puzzling is the PPP puzzle? An alternative half-life measure of convergence to PPP - Georgios E. Chortareas; George Kapetanios (Queen Mary University of London, Department of Economics, 2004)
The lengthy half-lives of real exchange rates in the presence of high degree of exchange rate volatility has been considered as one of the most puzzling empirical regularities in international macroeconomics. This paper suggests that the measure of half-life used in the literature might be problematic and suggests an alternative measure. Empirical analysis suggests that use of the new measure may shed light on the PPP puzzle.
Keywords: C12; C15; C23; 330; PPP; Half life; Real exchange rates; Kaufkraftparit\~AƒÂt; Wechselkurs; Volatilit\~AƒÂt; Sch\~AƒÂtzung; USA